Architectural Strategies for Scalable, Secure, and High-Performance Software Systems - Jaenudin, Jejen; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2025)
Software Architecture is a discipline within software development that focuses on the structure and interaction of system components. It encompasses decision-making that impacts the technical design, functionality, performance, and scalability of the system. The aim of software architecture is to ensure that the system can meet both business and technical requirements efficiently and effectively. Key components in software architecture include modules, components, and services, as well as their relationships, often depicted through architectural diagrams. This approach also involves considerations for various non-functional factors such as security, reliability, and change management. A well-defined architecture enables development teams to better understand and manage system complexity, enhancing collaboration and communication among team members. Furthermore, robust software architecture can extend the system’s lifespan and reduce maintenance and development costs in the future.